2007
DOI: 10.1038/sj.jid.5700859
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylfumarate Specifically Inhibits the Mitogen and Stress-Activated Kinases 1 and 2 (MSK1/2): Possible Role for its Anti-Psoriatic Effect

Abstract: The p38 mitogen-activated protein kinase (MAPK) signaling pathway, which regulates the activity of different transcriptions factors including NF-kappaB, is activated in lesional psoriatic skin. The purpose of this study was to investigate the effect of fumaric acid esters (FAEs) on the p38 MAPK and the downstream kinases mitogen- and stress-activated protein kinase (MSK)1 and 2 in cultured human keratinocytes. Cell cultures were incubated with dimethylfumarate (DMF), methylhydrogenfumarate (MHF), or fumaric ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 44 publications
(69 reference statements)
1
74
1
Order By: Relevance
“…7, Point 2). Our observation is in conflict with a study published by Gesser et al (47) where DMF inhibits MSK1 without affecting p38 or ERK1/2. However, different cell types and different stimuli may explain the difference we observed.…”
Section: Discussioncontrasting
confidence: 99%
“…7, Point 2). Our observation is in conflict with a study published by Gesser et al (47) where DMF inhibits MSK1 without affecting p38 or ERK1/2. However, different cell types and different stimuli may explain the difference we observed.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, MSK-1 phosphorylation at the Ser360 and Thr581 phosphorylation sites, which are directly targeted by p38 or ERK MAPK [28], were not affected by DMF treatment. These findings are in agreement with another study in keratinocytes, showing that DMF inhibited MSK-1 phosphorylation at Ser376 independently of p38 or ERK MAPK [21]. MKP-1, an endogenous inhibitor of MAPK, can be upregulated by reduced GSH levels [29] and, besides inhibiting MAPK p38 and ERK in ASMCs [23], it was reported to dephosphorylate histone H3 at Ser10 [30].…”
Section: Discussionsupporting
confidence: 91%
“…Previously, it was shown that DMF inhibits the phosphorylation of MSK-1 at Ser376, resulting in reduced phosphorylation of downstream CREB (cyclic adenosine monophosphate response element binding) and NF-kB p65 [7,21]. MSK-1 also phosphorylates histone H3 at Ser10 [20], which increases the accessibility of NF-kB binding sites within different promoters [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blotting analysis revealed a consistent and significant increase in phosphorylated MSK1 (Ser376) in lesional psoriatic skin [78,79]. Cultured human keratinocytes incubated with anisomycin or IL-1β resulted in the phosphorylation of both p38 MAPK and MSK1 (Ser376) whereas MSK1 (Ser376) phosphorylation was inhibited by pre-incubation with p38 inhibitors or dimethylfumarate [80]. In addition, transcription factors, such as cAMP/calcium responsive element binding protein (CREB) associated with cellular proliferation gene expression, are also phosphorylated in psoriatic skin [81].…”
Section: P38 Mapk In Psoriasis and Psoriatic Arthritismentioning
confidence: 94%